Widespread collapse, glimpses of revival: a scoping review of mental health policy and service development in Central Asia - Aliev, Akmal-Alikhan; Roberts, Tessa; Magzumova, Shakhnoza; Panteleeva, Liliia; Yeshimbetova, Saida; Krupchanka, Dzmitry; Sartorius, Norman; Thornicroft, Graham; Winkler, Petr (Social psychiatry and psychiatric epidemiology, 2021)
PURPOSE: We aimed to map evidence on the development of mental health care in Central Asia after 1991. METHOD: We conducted a scoping review complemented by an expert review. We searched five databases for peer-reviewed journal articles and conducted grey literature searching. The reference lists of included articles were screened for additional relevant publications. RESULTS: We included 53 articles (Kazakhstan: 13, Kyrgyzstan: 14, Tajikistan: 10, Uzbekistan: 9, Turkmenistan: 2, Multinational: 5). Only 9 were published in internationally recognised journals. In the 1990's mental health services collapsed following a sharp decline in funding, and historically popular folk services re-emerged as an alternative. Currently, modernised mental health policies exist but remain largely unimplemented due to lack of investment and low prioritisation by governments. Psychiatric treatment is still concentrated in hospitals, and community-based and psycho-social services are almost entirely unavailable. Stigma is reportedly high throughout the region, psychiatric myths are widespread, and societal awareness of human rights is low. With the exception of Kyrgyzstan, user involvement is virtually absent. After many years of stagnation, however, political interest in mental health is beginning to show, along with some promising service developments. CONCLUSIONS: There is a substantial knowledge gap in the region. Informed decision-making and collaboration with stakeholders is necessary to facilitate future reform implementation.
Keywords: Kazakhstan; zdravotní politika; Turkmenistan; Mental health; Kazachstán; Central Asia; Kyrgyzstan; Health Policy; Tádžikistán; Humans; Kyrgyzstán; Uzbekistan; Uzbekistán; Turkmenistán; Tajikistan; lidé; Deinstitutionalization